2015
DOI: 10.1073/pnas.1508114112
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic humans transmit dengue virus to mosquitoes

Abstract: Three-quarters of the estimated 390 million dengue virus (DENV) infections each year are clinically inapparent. People with inapparent dengue virus infections are generally considered dead-end hosts for transmission because they do not reach sufficiently high viremia levels to infect mosquitoes. Here, we show that, despite their lower average level of viremia, asymptomatic people can be infectious to mosquitoes. Moreover, at a given level of viremia, DENV-infected people with no detectable symptoms or before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
392
4
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(420 citation statements)
references
References 33 publications
17
392
4
7
Order By: Relevance
“…For example, the ID 50 for DENV-1 and DENV-2 was lower than for DENV-3 and DENV-4 in one study in Vietnam [36], and field populations of A. aegypti demonstrated lower vector competence for the American genotype of DENV-2 than the Southeast Asian genotype [37]. It has been shown that people with asymptomatic and presymptomatic DENV infections had an approximately 100-fold lower ID 50 and resulted in larger viral loads in infected mosquitoes, which was interpreted as increased transmission potential [38].…”
Section: Vector Competencementioning
confidence: 99%
“…For example, the ID 50 for DENV-1 and DENV-2 was lower than for DENV-3 and DENV-4 in one study in Vietnam [36], and field populations of A. aegypti demonstrated lower vector competence for the American genotype of DENV-2 than the Southeast Asian genotype [37]. It has been shown that people with asymptomatic and presymptomatic DENV infections had an approximately 100-fold lower ID 50 and resulted in larger viral loads in infected mosquitoes, which was interpreted as increased transmission potential [38].…”
Section: Vector Competencementioning
confidence: 99%
“…and In (2), is the transmission probability of CHK and , , , > 1 are the modification parameters accounting for the assumption that infected humans and mosquitoes are more infectious than exposed humans and mosquitoes, respectively (Duong et al, 2015). Furthermore, is the per capita biting rate of female mosquito on the human host per unit time.…”
Section: Special Conference Edition November 2017mentioning
confidence: 99%
“…[62,63] Moreover, a 2015 study revealed that people with asymptomatic DENV infections can still infect biting mosquitoes. [64] Visitors or returning residents may infect blood-feeding Ae. aegypti without displaying signs of illness.…”
Section: Back-to-the-future Potential For Autochthonous Transmission Ofmentioning
confidence: 99%